Implementasi Sistem Online Single Submission Risked Based Approach (OSS RBA) Di Kantor Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kota Tanjungpinang - Revanza Salsa Bilita; Fazriyan Nurazmi; Indra Prasta (CiDEA Journal, 2023)
This study aims to determine the implementation of the online single submission system risk based approach at Dimas investment integrated one door service of Tanjungpinang city, based on the type of data, this research includes quantitative research, data collection techniques used in the form of literature studies. Based on this research, it can be concluded that the implementation of the online single submission risk-based approach system has gone well. This can be seen from several aspects. First, in terms of organization, PTSP has prepared an implementation team whose task is to assist businesses in the process of inputting and verifying information when errors occur. Second, in terms of interpretation, the PTSP has succeeded in directing business actors to follow the stages in OSS-RBA.. Thus, the results of this study indicate that the implementation of the risk-based approach online single submission system has been successful in facilitating business actors in obtaining business licenses through OSS-RBA.